Experimental validation of a three-phase induction motor operating with a three-phase bidirectional variable speed drive - Machado, Luís Filipe Carvalho (2021)
The three-phase induction motor is the main electric motor used in industrial applications, contributing significantly to the industrial electricity consumption. Additionally, the traditional variable speed drivers, due to the internal constitution based on a passive rectifier, contribute to accentuate power quality problems on the grid side. In this context, this paper presents thesimulation, implementation and subsequent experimental verification of an electronic variable speed drive for three-phase induction motors, which is composed by a three-phase ac-dc converter on the grid side and by a three-phase dc-ac converter on the motor side. With the proposed solution, besides driving the motor, it is possible to mitigate power quality problems on the grid side (e.g., current harmonics and reactive power) associated with the use of diode-bridge ac-dc converters in the conventional variable speed drives. Besides, with the proposed solution, a bidirectional operation is possible, allowing to deliver to the power grid the energy generated in motor braking processes. As demonstrated along the paper, with the proposed variable speed drive it is possible to control the motor speed (including the rotation direction), and to achieve operation with sinusoidal currents and unitary power factor on the grid side. A laboratory prototype was developed, allowing to perform experimental validation and to verify the main functionalities of the variable speed drive